If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -4x + -6 = 2x + -1x Reorder the terms: 16 + -6 + -4x = 2x + -1x Combine like terms: 16 + -6 = 10 10 + -4x = 2x + -1x Combine like terms: 2x + -1x = 1x 10 + -4x = 1x Solving 10 + -4x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -4x + -1x = 1x + -1x Combine like terms: -4x + -1x = -5x 10 + -5x = 1x + -1x Combine like terms: 1x + -1x = 0 10 + -5x = 0 Add '-10' to each side of the equation. 10 + -10 + -5x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -5x = 0 + -10 -5x = 0 + -10 Combine like terms: 0 + -10 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 49x^2+35x+6=0 | | x^4+6x^3=9x^2+54x | | x+(x+2)+(x+4)=189 | | 5(x+4)+(x-5)=10 | | (x^4+6x^3)+(-9x^2-54x)=0 | | 6z+z=-7z-9+2z | | 2.50x+39.99=1.75x+50.00 | | 6+16x-1=9x+93-4x | | -18+3=-5(x+2) | | -9=-7z-6(2z+1) | | 4x+22=40 | | -6z+4z=9z+2+5z | | 250x+39.99=1.75x+50.00 | | 4(n+2)+9=5-3n | | n-4n=6 | | 6(9+2x)=7x+14 | | -(-7n+3)=-(-2+6n) | | 3x^2+40x-75=0 | | 7w+6=3(w-6) | | 8+8t=-2(t-6) | | 9s^2+90s-125=0 | | 2+x/3=0 | | 5x-45=2x | | (6x+8)^1/2=(5+2x)^1/2 | | (6x+8)^1/2=(5+2x)^1/5 | | 13x+17=13x-17 | | -2-10= | | -(-8q+2)=-2(-9-7q) | | 4x-32=-y | | 2(9q+3)=-2(2+3q)-2q | | 12x+2x=84 | | 24x^3+30x^2= |